CLEARING OF SMALL-SCALE TURBID COLOURED WATERS ON THE CONTACT AND BIOCLARIFYING FILTERS - Орлов, В. О.; Орлова, А. М.; Туровська, Г. І. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2011)
Theoretical substantiation and the results of studies on lightening and discoloration of natural small-scale turbid and non-ferrous water on the contact bioclarifying filters.